Poly(azomethine) Based Micelles for Delivery of Caffeic Acid Phenethyl Ester - Topuzogullari, Nermin Saliha; Poyraz, Fatma Sayan; Topuzogullari, Murat; Mansuroglu, Banu (POLYMER SOC KOREA, 2025)
Poly(azomethine) based micelles have been developed for the delivery of caffeic acid phenethyl ester (CAPE). These micelles, synthesized from a polyazomethine-PEG block copolymer, demonstrate significant potential in drug release systems due to its pH-sensitive biodegradable nature. Characterization through SEM revealed spherical micelles with an average diameter of 135.5 nm. The micelles' drug release behavior was studied at physiological (pH 7.2) and lysosomal (pH 5.0) pH levels. The findings indicated pH sensitive release of CAPE from the micelle of which only 2.14% of CAPE was released at pH 7.2 while 38.8% of CAPE was released at pH 5.0 after 24 h. In vitro cell viability assays using human-derived fibroblast cells showed that CAPE-loaded micelles exhibited minimal toxicity after 48 hours compared to CAPE and free micelle. These results suggest the potential of polyazomethine-based micelles as efficient carriers for targeted drug delivery for therapeutic purposes.
Keywords: drug delivery; micelle; pH-sensitive; polyazomethine; polyimine; BLOCK-COPOLYMER; STABILITY; CARRIER; POLYMER; RATS; Polymer Science